Rapidly progressed neuroendocrine carcinoma in the extrahepatic bile duct: a case report and review of the literature - Mariko Kamiya; Naoto Yamamoto; Yuto Kamioka; Hirohide Inoue; Hirokazu Yotsumoto; Masaaki Murakawa; Toru Aoyama; Kota Washimi; Kae Kawachi; Takashi Oshima; Makoto Ueno; Norio Yukawa; et al. (Surgical Case Reports, 2020)
Abstract Background Neuroendocrine carcinoma (NEC) originating from the extrahepatic bile duct (EHBD) is very rare but is known for its aggressiveness and poor prognosis. We herein report a case of rapidly progressed NEC in the extrahepatic bile duct. Case presentation An 84-year-old man was referred to our facility with obstructive jaundice and abdominal pain. Imaging studies revealed an irregular filling defect in the middle bile duct by endoscopic retrograde cholangiopancreatography and an enhanced wall thickening from the middle to distal portion by enhanced computed tomography. The patient was initially diagnosed with extrahepatic cholangiocarcinoma by a bile duct biopsy and underwent pancreatoduodenectomy with lymph node dissection. The pathological findings showed an NEC with an adenosquamous carcinoma component in the extrahepatic bile duct with lymph node metastases. The patient experienced multiple liver metastases 1 month after surgery and died 3 months after surgery. Due to the rapid progression of his disease, his general condition deteriorated, and he was unable to receive any additional treatments, such as chemotherapy. Conclusion As shown in our case, NEC of the EHBD has an extremely poor prognosis and can sometimes progress rapidly. Multimodality treatment should be considered, even in cases of locoregional disease.